23⋅(3y+6)=-6-3y

Apply the distributive property.

23(3y)+23⋅6=-6-3y

Cancel the common factor of 3.

Factor 3 out of 3y.

23(3(y))+23⋅6=-6-3y

Cancel the common factor.

23(3y)+23⋅6=-6-3y

Rewrite the expression.

2y+23⋅6=-6-3y

2y+23⋅6=-6-3y

Cancel the common factor of 3.

Factor 3 out of 6.

2y+23⋅(3(2))=-6-3y

Cancel the common factor.

2y+23⋅(3⋅2)=-6-3y

Rewrite the expression.

2y+2⋅2=-6-3y

2y+2⋅2=-6-3y

Multiply 2 by 2.

2y+4=-6-3y

2y+4=-6-3y

Add 3y to both sides of the equation.

2y+4+3y=-6

Add 2y and 3y.

5y+4=-6

5y+4=-6

Subtract 4 from both sides of the equation.

5y=-6-4

Subtract 4 from -6.

5y=-10

5y=-10

Divide each term in 5y=-10 by 5.

5y5=-105

Cancel the common factor of 5.

Cancel the common factor.

5y5=-105

Divide y by 1.

y=-105

y=-105

Divide -10 by 5.

y=-2

y=-2

Solve for y 2/3*(3y+6)=-6-3y